Performance of Malaria Volunteers regarding Malaria Control Activities in Southeastern Myanmar: A Study in the Areas under Coverage of an Ethnic Health Organization - Ye Thiha; Thant Zin; Kyawt Mon Win; Myat Thu Soe; Pyae Linn Aung (Journal of Tropical Medicine)
Malaria volunteers (MVs) play an essential role in resolving malaria problems by delivering greater access to diagnosis and treatment services, mainly for the underserved community residing in hard-to-reach rural areas. The Karen Department of Health and Welfare (KDHW) has implemented community-based malaria control activities among the ethnic minorities in southeastern Myanmar by promoting the roles of MVs. This study aimed to explore the factors influencing the performance of MVs regarding malaria control activities in the area. From July to August 2019, a cross-sectional study was conducted in 12 townships of southeastern Myanmar under the umbrella of the KDHW malaria project. A total of 140 MVs were employed as study participants. Data were collected through face-to-face interviews using a structured questionnaire. For data analyses, descriptive statistics, chi-squared tests, and logistics regression models were applied. More than half of the MVs perceived a good level of performance on malaria control activities. A higher level of performance has been observed among the MVs who had another job (AOR: 1.9, 95% CI: 1.2–3.9), those experienced in health-related fields (AOR: 1.9, 95% CI: 1.4–4.9), who received good community support (AOR: 2.1, 95% CI: 1.3–10.9), who were volunteers beyond three years (AOR: 4.0, 95% CI: 2.8–9.2), and whose family income totaled over 500,000 MMK (AOR: 2.8, 95% CI: 1.6–4.2). The results mentioned the characteristics which should be prioritized in recruiting MVs. MV network and their workforce need to be nurtured by encouraging community support. For performance sustainability, attractive incentive schemes or a salary should be subsidized in support of their livelihoods.